Changes in blood flow distribution after hypogastric artery embolization and the ischaemic tolerance of the pelvic circulation. Issue 5 (February 2019) - Nitta, Jun; Hoshina, Katsuyuki; Isaji, Toshihiko
Abstract : Abstract: This study aimed to compare the pelvic cavity vasculature before and after the interventional occlusion of a hypogastric artery (IOHA) and to reveal the protective mechanism of the collateral vessels against pelvic ischaemia. Sixty-nine patients with abdominal aortic or aortoiliac aneurysms who underwent endovascular aneurysm repair accompanied with IOHA were retrospectively analysed. Patients were divided into those who complained of buttock claudication (BC) group and asymptomatic patients (non-BC group). Two analyses were performed. In Study 1, the factors associated with postoperative BC were evaluated in patients who underwent IOHA using only 0.035 Tornade embolization coils. In Study 2, the pelvic arterial volume (PAV) was assessed in patients with both pre- and postoperative multidetector computed tomography images. PAV was calculated by subtracting the aortoiliac artery volume from the total PAV. The PAV ratio was defined as the postoperative PAV divided by preoperative PAV and represented collateral development in the pelvis. In Study 1, BC occurred in 16 patients (BC group) and did not occur in 25 patients (non-BC group). Significantly more coils were used in the BC group than in the non-BC group (8.6 ± 1.0 vs 5.6 ± 0.83, P  = .013). Study 2 had 24 patients in the BC group and 31 patients in the non-BC group. The PAV ratio was significantly higher in the BC group than in the non-BC group (0.93 ± 0.05 vs 0.62 ± 0.04, P <.0001). The use of more coils in IOHA is associated with BC. In addition, volumetric analysis revealed that less collateral vessel development occurred in the non-BC group than in the BC group, which might reflect a potential reservation capacity of non-BC patients for acute pelvic ischaemia.